Anatomy of a murder [videorecording (DVD)] - Ellington, Duke, 1899-1974 (Criterion collection, 2012)
A small-town Michigan lawyer takes on a difficult case: that of a young Army lieutenant accused of murdering the local tavern owner who he believes raped his wife. A gripping, envelope-pushing courtroom drama, Anatomy of a murder was groundbreaking for the frankness of its discussion of sex. More than anything else, it is a striking depiction of the power of words. With its outstanding supporting cast and influential jazz score by Duke Ellington, it is an American movie landmark.